Mental Health Clinical Pastoral Education—A Specialized CPE Program - Angelika A. Zollfrank; Caroline C. Kaufman; David H. Rosmarin (Religions, 2025)
This article describes the design and implementation of a Specialized Mental Health Clinical Pastoral Education (CPE) program for clergy and theological students of all spiritual, religious, and cultural backgrounds. Addressing the need for mental health competencies in religious leaders and chaplains, this training equips participants with specialized skills in individual and group mental health spiritual assessment and spiritual care. Program participants become effective members of a multiprofessional team, gain knowledge of mental health philosophies of concordant and discordant spiritual orienting systems, and gain greater relational capacity. The Mental Health CPE Program includes traditional and novel CPE elements: (1) clinical practice, (2) group and individual supervision, (3) didactic presentations and journal clubs, (4) verbatim (Protocols of patient encounters) and case presentations, (5) group leadership training and practica, and (6) experience of faith reflections. This article provides insights into the origins of CPE, a description of the implementation in a free-standing psychiatric hospital, and observed developmental changes of program participants. We include graduates’ anecdotal feedback about their learning experience and its impact on their leadership in chaplaincy and in religious communities. Additionally, we report on areas for future development and further study of the effectiveness of Mental Health CPE.